2018
DOI: 10.1002/etc.4233
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of methylmercury in the muscle tissue of freshwater fish varies with body size and age and among species

Abstract: It is commonly assumed that most (>95%) of the mercury (Hg) found in fish muscle is the toxic form, methylmercury (MeHg), due to its efficient assimilation and retention in biotic tissue. However, this assumption is largely based on studies examining the percentage of MeHg (%MeHg [the fraction of total Hg as MeHg]) in muscle from mostly large-bodied predatory fish; less is known about the %MeHg in smaller bodied individuals or those of different trophic guilds. The present study analyzed MeHg and total Hg conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 59 publications
(88 reference statements)
2
34
0
1
Order By: Relevance
“…Duplicate samples were analysed every 20 samples, and the mean relative difference percentage was 9.23% ± 8.12% (range 0.04-28.22%; n = 20) ( Supplementary Table S4). Total mercury (THg) was used as a proxy for methylmercury (MeHg) since previous studies have found that most of the THg in fish tissue is MeHg (i.e., > 95% 54 ; 83.5 ± 19.7% 35 ; 68.1-88.8% 34,36 ). The assumption that > 90% of THg is MeHg applies to predatory species but does not necessarily apply to young fish and to fish from lower trophic levels where the percentage of MeHg is lower 35 .…”
Section: Mercury Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Duplicate samples were analysed every 20 samples, and the mean relative difference percentage was 9.23% ± 8.12% (range 0.04-28.22%; n = 20) ( Supplementary Table S4). Total mercury (THg) was used as a proxy for methylmercury (MeHg) since previous studies have found that most of the THg in fish tissue is MeHg (i.e., > 95% 54 ; 83.5 ± 19.7% 35 ; 68.1-88.8% 34,36 ). The assumption that > 90% of THg is MeHg applies to predatory species but does not necessarily apply to young fish and to fish from lower trophic levels where the percentage of MeHg is lower 35 .…”
Section: Mercury Methodsmentioning
confidence: 99%
“…Total mercury (THg) was used as a proxy for methylmercury (MeHg) since previous studies have found that most of the THg in fish tissue is MeHg (i.e., > 95% 54 ; 83.5 ± 19.7% 35 ; 68.1-88.8% 34,36 ). The assumption that > 90% of THg is MeHg applies to predatory species but does not necessarily apply to young fish and to fish from lower trophic levels where the percentage of MeHg is lower 35 . Thus, assuming that > 90% of THg is MeHg for lower trophic level fish (i.e., Flathead Grey Mullet) would overestimate the risk to consumers.…”
Section: Mercury Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the findings from the focus group data in Table 2, food consumption was grouped for the fish, land animal and bird categories by preparation type (cooked; smoked), and by type of fish in the food chain (predatory, non-predatory), potentially having an impact on the dose reconstruction of mercury exposure as predatory fish generally have mercury levels that are higher than those in non-predatory fish [22]. Cooked fish tended to be more frequently consumed than smoked fish and the meats from wild game were more frequently consumed than fish and game birds.…”
Section: Refinement Of the Ffqmentioning
confidence: 99%